Purification, Characterization, Identification, and Anticancer Activity of a Circular Bacteriocin From Enterococcus thailandicus - Al-Madboly, Lamiaa A.; El-Deeb, Nehal M.; Kabbash, Amal; Nael, Manal A.; Kenawy, Ahmed M.; Ragab, Amany E. (Frontiers in Bioengineering and Biotechnology, 2020)
New anticancer agents are continually needed because cancerous cells continue to evolve resistance to the currently available chemotherapeutic agents. The aim of the present study was to screen, purify and characterize a hepatotoxic bacteriocin from Enterococcus species. The production of bacteriocin from the Enterococcus isolates was achieved based on their antibacterial activity against indicator reference strains. Enterococcus isolates showed a broad spectrum of antibacterial activity by forming inhibition zones with diameters ranged between 12-29 mm. The most potent bacteriocin produced strain was molecularly identified as Enterococcus thailandicus. The crude extracted bacteriocin was purified by cation exchange and size exclusion chromatography that resulted in 83 fractions. Among them, 18 factions were considered as bacteriocins based on their positive antibacterial effects. The anticancer effects of the purified bacteriocins were tested against HepG2 cell line. The most promising enterocin (LNS18) showed the highest anticancer effects against HepG2 cells (with 75.24% cellular inhibition percentages), with IC50 value 15.643 µM and without any significant cytotoxic effects on normal fibroblast cells (BJ ATCC® CRL-2522™). The mode of anticancer action of enterocin LNS18 against HepG2 cells could be explained by its efficacy to induce cellular ROS, decrease HepG2 CD markers and arrest cells in G0 phase. Amino acid sequencing of enterocin LNS18 was determined and the deduced peptide of the structural gene showed 86 amino acids that shared 94.7% identity with enterocin NKR-5-3B from E. faecium. Enterocin LNS18 consisted of 6 α-helices; 5 circular and one linear. Model-template alignment constructed between enterocin LNS18 and NKR-5-3B revealed 95.31% identity. The predicted 3D homology model of LNS18, after circularization and release of 22 amino acids, showed the formation of a bond between Leu23 and Trp86 amino acid residues at the site of circularization. Furthermore, areas of positive charges was due to the presence of 6 lysine residues resulting in a net positive charge of +4 on the bacteriocin surface. Based on the above mentioned results, our characterized bacteriocin is a promising agent to target liver cancer without any significant toxic effects on normal cell lines.